2014
DOI: 10.1007/s10750-013-1792-2
|View full text |Cite
|
Sign up to set email alerts
|

Fertile sediment and ammonium enrichment decrease the growth and biomechanical strength of submersed macrophyte Myriophyllum spicatum in an experiment

Abstract: Decline of submersed macrophytes has occurred in eutrophic lakes worldwide. Little is known about effects of nutrient enrichment on biomechanical properties of submersed macrophytes. In a 30-day experiment, Myriophyllum spicatum was cultured in aquaria containing two types of sediment (mesotrophic clay vs. fertile loam) with contrasting water NH 4 ? concentrations (0 vs. 3.0 mg L -1 NH 4 -N). The plant growth, shoot and root morphology, stem biomechanical properties, and stem total nonstructure carbohydrates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Finally, the simple recovery or maintenance of riparian vegetation seems to be sufficient to prevent U. arrecta invasion, as suggested by our shading treatments. Our results align with others that indicate that increased shading is an effective strategy to reduce invasion by macrophytes (Bunn et al 1998;Schooler 2008;Zhu et al 2014;Zefferman 2015).…”
Section: A N a G E M E N T I M P L I C A T I O N Ssupporting
confidence: 92%
“…Finally, the simple recovery or maintenance of riparian vegetation seems to be sufficient to prevent U. arrecta invasion, as suggested by our shading treatments. Our results align with others that indicate that increased shading is an effective strategy to reduce invasion by macrophytes (Bunn et al 1998;Schooler 2008;Zhu et al 2014;Zefferman 2015).…”
Section: A N a G E M E N T I M P L I C A T I O N Ssupporting
confidence: 92%
“…natans is often the dominant macrophyte in eutrophic Chinese lakes and was selected for use in our experiment as it is among the last plants to disappear when eutrophication leads to complete loss of submerged macrophyte [16]. Other plant species may be even more sensitive and fragile as has been demonstrated in experiments with Myriophyllum spicatum [47] and Potamogeton crispus [48]. Our small-scale experiment has limitations since plant-nutrient interactions may be stronger in mesocosms than in natural lakes, but the observed direction of change is supported by findings in both experiments at larger scale and in the field [26,42].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, similar to the stems of submerged macrophytes (e.g. Hydrilla verticillata, M. spicatum and Potamogeton malaianus) in previous studies (Miler et al 2014;Zhu et al 2012aZhu et al , 2014, V. natans also showed reduced biomechanical properties along the leaves, which indicate that upper leaves were more fragile and vulnerable to hydraulic damage, as hydraulic forces acting on submerged macrophytes stands decrease exponentially with water depth (Denny 1988;Schutten et al 2004). Consequently, the various biomechanical properties of V. natans leaves, in part, explain its distribution pattern in Lake Erhai.…”
Section: Discussionmentioning
confidence: 62%
“…It suggested that both stronger and more flexible leaves are necessary for V. natans to survive under a high and longer time wind exposure, just like other aquatic plants in rivers (Miler et al 2012) such as Fontinalis antipyretica grown in fierce water flow that had higher flexibility of stems than other species. Once the drag forces exceed the tensile force or tensile strain of plants, shoot breakage will incur, thus reduced fitness, due to loss of biomass and meristems (Mony et al 2011;Zhu et al 2014). Unlike other submerged macrophytes species, shoot breakage is fatal to the survival of V. natans, because it is rosette species (leaves inserted on a reduced, partly buried stem, Sun 1995), therefore, the leaf fragment of V. natans cannot re-sprout, not to mention become a new plant.…”
Section: Discussionmentioning
confidence: 99%